Histone demethylases and control of gene expression in plants - Prakash, S.; Singh, R.; Lodhi, N. (Cellular and Molecular Biology, 2014)
Covalent histone modifications, chromatin remodeling and incorporation of histone variants regulate the dynamics of chromatin structure. Among covalent histone modifications, histone methylation mediates by histone methylases that influence the gene expression in heterochromatin silencing, genomic imprinting and transcription. In contrast to methylases, histone demethylases remove the methyl groups from lysine or arginine residues of histones and have enormous impact on gene expression via modified chromatin structures. Two types of histone lysie demethylases have been identified, including lysine specific demethylases 1 (LSD1) and Jmj (Jumonji) domain containing family proteins. The human demethyliminase (PADI4) converts monomethyl arginine residue to citrulline by the arginine demethylimination. In this review we summarize recent advances to understand the mechanism of demethylases in regulation of plant gene expression. In addition we are highlighting the function of four human like LSD1 (LDL) and jmj domain containing genes of Arabidopsis that regulate the defense related, flowering controlling and brassinosteroid response genes.